STRATEGIES FOR MANAGING CHANGE IN HUMAN RESOURCE MANAGEMENT IN INDONESIAN HIGHER EDUCATION: A SYSTEMATIC LITERATURE REVIEW (SLR) - Sofyan Sauri; Muhammad Gunawan Wibisono (Indonesian Naval Technology College STTAL, 2024)
Managing change in human resource management (HRM) is a crucial aspect for the sustainability and advancement of institutions, particularly in educational settings such as universities. This study aims to reveal effective strategies for managing change within such environments, focusing on a case study of developments in a higher education institution. In this dynamic era, understanding and applying appropriate strategies is key to ensuring successful adaptation and innovation amidst ongoing changes. HRM is a primary pillar in maintaining an organization's continuity and progress. Amidst the constant flux of change, strategic HRM becomes increasingly important, serving not only as a guide but also as a foundation that enables organizations to adapt, grow, and succeed in an ever-changing environment. This research offers valuable insights into HRM strategies by deeply understanding how organizations manage their human resources, both in specific contexts like universities and in broader scopes. By identifying successful patterns, potential obstacles, and opportunities for innovation (Wang, Z., Xu, H., & Song, M., 2021), this study provides essential knowledge. Case studies, such as the one detailed in this article, offer concrete insights. By examining specific development cases in universities, we learn about strategic steps such as organizational restructuring, employee development, effective communication, and active stakeholder engagement, each significantly impacting organizational well-being. Therefore, this research aims to explore how these strategies are understood, adopted, and adjusted within the context of universities. It is hoped that a profound understanding of HRM strategies will contribute positively to sustainable and innovative managerial practices in the future. The study employs a systematic and comprehensive literature review approach using the SCOPUS database, considered credible and internationally indexed, to identify research trends and developments in HRM strategies. This methodology ensures an objective, transparent, and replicable analysis, providing a rich and beneficial contribution to the field of strategic HRM in higher education.